Perkin-Elmer differential scanning calorimeter with robotic autosampler - Perkin-Elmer Corporation (1986)
General view of a Perkin-Elmer differential scanning calorimeter with a robotic autosampler in use at an unidentified laboratory facility. The individual visible in the photograph is identified as Mike DeVito.
Keywords: Calorimeters; Employees; Perkin-Elmer Corporation; Laboratories; Corporations; Calorimetry; Scientific apparatus and instruments